Clinical value of Hospital Admission Risk Profile (HARP) and the Identification of Seniors at Risk (ISAR) scales to predict hospital-associated functional decline in an acute geriatric unit in Colombia (Colombia Medica, 2023)
Background:Older adults admitted to a hospital for acute illness are at higher risk of hospital-associated functional decline during stays and after dischargeObjective:This study aimed to assess the calibration and discriminative abilities of the Hospital Admission Risk Profile (HARP) and the Identification of Seniors at Risk (ISAR) scales as predictors of hospital-associated functional decline at discharge in a cohort of patients older than 65 receiving management in an acute geriatric care unit in Colombia.Methods:This study is an external validation of ISAR and HARP prediction models in a cohort of patients over 65 years managed in an acute geriatric care unit. The study included patients with the Barthel index measured at admission and discharge. The evaluation discriminates ability and calibration, two fundamental aspects of the scales.Results:Of 833 patients evaluated, 363 (43.6%) presented hospital-associated functional decline at discharge. The HARP underestimated the risk of hospital-associated functional decline for patients in low- and intermediate-risk categories (relation between observed/expected events (ROE) 1.82 and 1.51, respectively). The HARP overestimated the risk of hospital-associated functional decline for patients in the high-risk category (ROE 0.91). The ISAR underestimated the risk of hospital-associated functional decline for patients in low- and high-risk categories (ROE 1.59 and 1.11). Both scales showed poor discriminative ability, with an area under the curve (AUC) between 0.55 and 0.60.Conclusion:This study found that HARP and ISAR scales have limited discriminative ability to predict HAFD at discharge. The HARP and ISAR scales should be used cautiously in the Colombian population since they underestimate the risk of hospital-associated functional decline and have low discriminative ability.